SOCIO ECONOMIC STATUS AND ITS IMPACT ON CULTURAL ACTIVITY OF BARAK VALLEY - Singha, Manindra (International Journal For Research In Business, Management And Accounting, 2019)
The present study is the explains of Manipuri culture and traditions which are going to be in a diverted way, but people of the society are very much aware of to save the dignity and honour and customs in the same in extent way like earlier. This attempt will be save customary traditional way life to keep unchanged scenario in the society. People of the Manipuri society is now in a way of transition period of modern process of living with materialistic world and with colourful ultra modern and dynamics of the new economic forces had been forcing in the activity which are not authorize by the community law. Moreover this work attempted to construct a reliable socio economic history and its impact on the culture of the Manipuri community of Assam and Tripura. Especially in the field of social events and ritual activity, if we find that un necessary expenditure and objectionable many things are likely to introduce un-authorizely in the every ritual rite.